IgA autoimmunity and coagulation among post-acute sequelae of SARS-CoV-2 infection (PASC) patients with persistent respiratory symptoms: a case-control study - Gomes, Claudia; Whiteson, Jonathan H.; Ponzo, Fabio; Condos, Rany; Ortigoza, Mila B.; Zuniga, Marisol; Rodriguez, Ana; Lee, David C. (Frontiers in Immunology, 2025)
IntroductionThe SARS-CoV-2 virus resulted in significant disability and diagnostic challenges among patients with Post-Acute Sequelae of COVID-19 (PASC). Here, we assessed microvascular perfusion, clotting, and autoimmune responses to lung targets in PASC patients compared to healthy controls with the aim of explaining the persistent respiratory symptoms of patients with PASC.MethodsWe performed a blinded case-control study of 20 PASC patients with persistent respiratory symptoms versus 20 healthy controls previously infected with SARS-CoV-2 virus. We assessed lung perfusion using Technetium-99m macroaggregated albumin (MAA) SPECT-CT scans, clotting using coagulation and thromboelastrogram (TEG) tests, and autoimmunity to vascular and lung antigens using ELISA assays.ResultsSubjective respiratory symptoms and quality-of-life measures were significantly worse among the PASC patients compared with healthy controls (p<0.001). Clinical symptoms among PASC patients were inversely correlated with plasma total IgA levels (coefficient: -0.61, p=0.004) and with autoimmune IgA recognizing pulmonary microvascular endothelial cell antigens (coefficient: -0.51, p=0.02). Additionally, levels of total IgA were directly correlated with fibrinogen and fibrin-related clot strength (coefficient: +0.52, p=0.02; coefficient: +0.63, p=0.003). SPECT-CT scans were positive only among 25% of PASC cases versus 10% of healthy controls (p=0.41). TEG tests showed no differences between the groups.ConclusionsOur small study of PASC patients identified that circulating IgA antibodies may correlate inversely with clinical symptoms and directly with clotting parameters, suggesting a possible link between autoimmunity and coagulation. However, many of the study’s findings were null, which may mean that tissue-level studies or alternative explanations of PASC need to be explored.